Anti-inflammatory effect of hydrogen sulfide donor sodium-sulfide in an experimental mouse model of contact hypersensitivity - Nermin Ozlen; Deniz Ercetin; Melike Sapmaz-Metin; Ozgur Gunduz (Wolters Kluwer Medknow Publications, 2023)
Background: Hydrogen sulfide (H2S), synthesized by most immune cells, has been shown to exert anti-inflammatory and antipruritic effects. The effect of H2S on allergic contact dermatitis (ACD), an inflammatory skin disease that negatively affects the quality of life, is unknown. Objectives: We planned to investigate the antipruritic and anti-inflammatory effects of the H2S donor sodium sulfide (Na2S) in the experimental mouse model of contact hypersensitivity (CHS), which is widely used for ACD research. Methods: CHS was created in Balb/c mice using 1-fluoro-2, 4-dinitrobenzene. Na2S was administered systemically (0.2-2-20 mg/kg/i.p.) and locally (1-3-10 nmol/both ear/i.d.) at 3 h and 25 h after the challenge. Ear thickness and the number of scratches were determined at 24 h and 48 h following the challenge. Ear tissue and serum interferon-gamma, interleukin (IL)-2, IL-4, and IL-5 cytokine levels were evaluated by enzyme-linked immunosorbent assay (ELISA). H and E staining was performed for histopathological studies. CD4+ and CD8+ T cells located in the skin were examined by immunohistochemical staining. Results: Locally (1-3-10 nmol/ear/i.d., P < 0.001, P < 0.0001, P < 0.0001, respectively) and systemically (2-20 mg/kg/i.p., P < 0.01, P < 0.0001, respectively), Na2S administration decreased ear thickness dose dependently. Local (1-3-10 nmol/ear/i.d.) Na2S treatment decreased serum IL-2 levels (P < 0.01, P < 0.05, and P < 0.01, respectively). Na2S administered locally (3-10 nmol/ear/i.d., P < 0.05) and systemically (20 mg/kg/i. p., P < 0.05) decreased the number of CD4+ T lymphocytes. Conclusion: Locally and systemically administered Na2S reduces ear thickness, which is one of the symptoms of CHS, probably by preventing CD4+ T lymphocyte infiltration and proliferation and decreasing IL-2 synthesis.